Balancing the Risk-Benefit Ratio of Immune Checkpoint Inhibitor and Anti-VEGF Combination Therapy in Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Tao, Li; Zhang, Huiyun; An, Guangyu; Lan, Haoning; Xu, Yaoqi; Ge, Yang; Yao, Jiannan (Frontiers in Oncology, 2021)
Background: Although immune checkpoint inhibitors (ICIs) combined with vascular endothelial growth factor receptor (VEGFR) targeted therapy and Sunitinib monotherapy have been widely applied to metastatic renal cell carcinoma (mRCC), effectiveness and safety data are still lacking. To optimize clinical decision-making, we conducted a systematic review and meta-analysis of published randomized clinical trials to characterize the efficacy and the risk of adverse events (AEs) in patients treated with ICIs plus anti-VEGF therapy. Materials and methods: We used PubMed, EMBASE, and the Cochrane Library to retrieve randomized controlled trials (RCTs) published before March 27, 2021. The efficacy outcomes were progression-free survival (PFS), overall survival (OS) and objective response rate (ORR). The pooled risk ratio (RR) and 95% confidence intervals of AEs were calculated in the safety analysis. Results: Six RCTs involving 4227 patients were identified after a systematic search. For OS, ICI and anti-VEGF combination therapy decreased mortality approximately 30% in the intention-to-treat population (ITT) (HR=0.70, 95%CI: 0.57-0.87), but there was no statistical difference in patients evaluated as ‘favorable’ by International Metastatic Renal-cell Carcinoma Database Consortium (IMDC) criteria compared with monotherapy (HR=0.90, 95%CI: 0.55-1.46, P=0.66). In terms of PFS, the progression risk for all participants declined 35% (HR=0.65, 95%CI: 0.50-0.83) and patients evaluated as 'poor' by IMDC benefited further (HR=0.46, 95%CI: 0.36-0.58). No evident divergence was found in age and sex subgroups. The RRs of all-grade hypertension, arthralgia, rash, proteinuria, high-grade (grade three - five) arthralgia, and proteinuria developed after combination therapy were increased compared with Sunitinib. The risk of high-grade hypertension and rash showed no statistical difference. However, the risk of hand-foot skin reaction (HFSR), stomatitis, and dysgeusia decreased in combination therapy groups. Conclusions: Compared with Sunitinib, OS, PFS and ORR were significantly improved in patients receiving ICI and anti-VEGF combination therapy at the expense of increased specific AEs. More attention should be paid to individualized application of these combination therapies to achieve the best benefit-risk ratio in the clinic.